Primary School English Teachers' Knowledge and Classroom Implementation of Oral Reading Fluency Instruction: A Mixed-Methods Study - Martha Budianto; Sarai Enita; Kaleb Priyanto (Simpati, 2026)
Oral reading fluency is a critical component of early literacy because it bridges decoding and reading comprehension. Despite its importance, fluency instruction remains one of the least emphasized aspects of early English reading instruction, particularly in English as a Foreign Language (EFL) primary classrooms. This study examined primary school English teachers' knowledge of oral reading fluency instruction and the factors influencing its classroom implementation. A convergent mixed-methods design was employed involving 20 English teachers from three purposively selected primary schools. Data were collected through structured classroom observations and semi-structured interviews. Observation data were analyzed using descriptive statistics, while interview data were analyzed thematically and integrated with the quantitative findings. The findings revealed that teachers possessed only partial knowledge of oral reading fluency, demonstrating stronger understanding of teacher modeling and reading rate than guided oral reading and prosody instruction. Classroom observations similarly showed limited implementation of evidence-based fluency strategies. Teachers identified insufficient pre-service preparation, limited professional development, large class sizes, and inadequate instructional resources as major barriers to effective fluency instruction. These findings highlight the need for stronger teacher preparation and professional development to support comprehensive oral reading fluency instruction in early English literacy classrooms.